γ1- and γ2-melanocyte stimulating hormones induce central anxiogenic effects and potentiate ethanol withdrawal responses in the elevated plus-maze test in mice - Jansone, Baiba; Rumaks, Juris; Dzirkale, Zane; Pupure, Jolanta; Svirskis, Šimons; Muceniece, Ruta; Klusa, Vija (Elsevier, 2009)
Little is known about the endogenous functions of γ1- and γ2-melanocyte stimulating hormones (γ1- and γ2-MSH). Although γ-MSHs bind to melanocortin receptor subtypes 3 and 4, we have previously shown that these peptides also influence non-melanocortinergic processes, such as dopaminergic and GABAergic. The aim of this study was to determine the effects of γ1- and γ2-MSH (at doses 0.3, 1 and 2 nmol/mouse/5 μl) on the anxiety levels in mice in elevated plus maze. Three experimental paradigms were performed to assess the effects of peptides on: a) ethanol withdrawal; b) acute ethanol-induced anxiolytic action; c) peptides per se. We used ethanol as the model substance, since its action involves either dopaminergic/GABAergic or melanocortinergic processes. γ-MSHs were administered intracisternally in mice and behavioural responses were assessed in the elevated plus maze test. This study provides the first demonstration of an anxiogenic effect of γ1- and γ2-MSH, their synergistic/additive effect on ethanol withdrawal-induced anxiety behaviour, and an antagonism of peptides involved in the anxiolytic action of ethanol. Furthermore, results suggest that γ-MSHs belong to an anxiogenic peptide family that may play an important role in anxiety disorders as well as in the development of alcohol dependence and/or alcohol withdrawal-induced behaviours.
Keywords: Research Subject Categories::MEDICINE; γ1-MSH; γ2-MSH; Anxiety; Ethanol withdrawal responses; Elevated plus-maze test